STRUKTUR GEOLOGI AREA BENCANA TANAH LONGSOR DI DESA TUMENGGAL, KECAMATAN PENGADEGAN-PURBALINGGA - Widagdo, Asmoro; Iswahyudi, Sachrul; Laksono, Anjar Tri (Institut Teknologi Adhi Tama Surabaya, 2021)
The Ligung Formation which is predominantly composed of claystone and the Kalibiuk Formation which is composed of volcanic breccias, both of which landslide simultaneously on the hillsides in the Tumenggal area, Pengadegan District, Purbalingga-Central Java. How the influence of the geological structure that has worked to compose the geological order of this area, which has an effect on the occurrence of the landslide, is the study that is revealed in this paper. Field observations of landslide locations were carried out by determining the position of the landslide, determining the type of bedrock, measuring the direction of the slope, measuring the dipping of rock layers and describing the distribution of landslides in the study area. The geological structures found in the study area are rock layers of the Ligung and Kalibiuk Formation and rock fractures/joints. Little dipping structure of the bed was observed in the field while intensive jointing was found in claystone. This structure has accelerated the weathering of claystone to form a thick soil. Andesite breccia found at the bottom of the slope has undergone intensive weathering. Rocks in the study area have a slope to the south and landslides to the north or towards the fore-slope, this is formed due to thick soil and intensive fractures/joints in the bedrock.